The luxury fashion fitting the mass-market: how luxury fashion bands can use social media masstige campaigns to leverage brand love - Veltman, Madalena Baptista (2021)
This thesis aims to understand whether if in the Luxury Fashion market masstige campaigns on social media can generate brand love. Furthermore, how can Luxury Fashion Brands build brand love when using masstige campaigns. To better understand these topics, this study includes some useful details from past research about luxury brands and its consumers, luxury fashion brands, social media, masstige campaigns, cognitive-affective response system (CAPS) and brand love. A survey questionnaire was spread online to collect primary data. This survey presented one of two randomized campaigns from the same brand: Prada or Prada x Adidas. Furthermore, the conceptual model proposes that attitude towards the brand, attitude towards the ad and consumer perceptions will influence the CAPS. Consequently, consumers will generate brand love based on the CAPS effects. The results provide valuable insights for Luxury Fashion Brands when thinking about conducting masstige campaigns on social media. Also, the overall findings of this thesis revealed that increasing the CAPS can lead to Brand Love. Thus, social media masstige campaign effectiveness can be reached when it comes to Brand Love.